On the Exact Boundary Control for the Linear Klein-Gordon Equation in Non-cylindrical Domains - Nunes, R. S. O. (Trends in Computational and Applied Mathematics, 2020)
The purpose of this paper is to study an exact boundary controllability problem in noncylindrical domains for the linear Klein-Gordon equation. Here, we work near of the extension techniques presented By J. Lagnese in [12] which is based in the Russell’s controllability method. The control time is obtained in any time greater then the value of the diameter of the domain on which the initial data are supported. The control is square integrable and acts on whole boundary and it is given by conormal derivative associated with the above-referenced wave operator.